HUBUNGAN FAKTOR PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT DENGAN STATUS GIZI BALITA - Mayarestya, Nita Putriasti; Ramli, Kamrianti; Suyati, Suyati; Indriani, Farihah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Malnutrition or stunting is a form of chronic malnutrition that occurs as a result of long-term nutritional deficiency. This condition generally arises when children receive inadequate nutrition in terms of both quantity and quality, thereby failing to meet their nutritional needs in accordance with their stage of growth and development. The purpose of this study was to determine the relationship between the implementation of clean and healthy living behaviors and the nutritional status of toddlers. This study used a cross-sectional design. The research was conducted in the working area of the Srandakan Community Health Center in February 2024. The population consisted of all families with toddlers. The sample consisted of 95 respondents. Simple random sampling was used as the sampling technique. The research instrument was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between clean and healthy living behaviors (p value: 0.043) and the nutritional status of toddlers. It is recommended that the Community Health Center improve the sources of information for mothers of toddlers about the nutritional status of children and the contributing factors by conducting regular health education and distributing leaflets or putting up posters. Keywords: Toddlers, Dietary Patterns, Nutritional Status